RISCOS OCUPACIONAIS NA EXTRAÇÃO DE MARISCOS NO MUNICIPIO DE SÃO JOSÉ DE RIBAMAR - MA - OLIVEIRA, Wallyson Rangel Ribeiro (2021)
Shellfishing is carried out under working conditions that present occupational risks that trigger health problems for workers, compromising their quality of social and professional life. This study aims to analyze occupational risks of shellfish extraction in the city of São José de Ribamar - MA. A bibliographic survey, visits and on-site observations, photographic records and application of questionnaires were carried out, with 18 closed and open questions. The data obtained were submitted to descriptive statistics parameters in which they were expressed in descriptive forms, percentages, tables and graphs. The workers in the shellfishing activity in Ribamar were mainly women, aged between 18 and 55 years old and had completed elementary school (60%). These workers had marital situations of singles with a family environment comprising an average of 1 to 3 children and an income of up to ½ minimum wage to 1 minimum wage. The shellfishing activity in Ribamar consists of two stages: shellfishing (separation of utensils, displacement to the mangrove, place of collection and shellfishing on said property) and processing (preparation, cooking, sambucagem, washing, weighing/packing and marketing). Workers in this activity were mainly exposed to occupational hazards of a biological and ergonomic nature and work accidents. These risks contributed to the development of pain in the back, lumbar region, neck and lower and upper limbs, as well as repetitive strain injuries and the presence of dermatitis and, among other health problems. It is concluded that the work environment of the shellfish collectors presented occupational risks, whose knowledge regarding these occupational risks helps in the systematization of mitigating and preventive measures to be applied according to the type of harmful agent, mitigating its effects and thus promoting the environment with conditions safe to carry out work activities and improve the quality of life of workers.